A Bibliographic Study on Tax Avoidance Research in Indonesia - Arham, mardianto; Firmansyah, Amrie; Nor, Aji M. Elvin; Vito, Bernadi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to map various research results related to tax avoidance in Indonesia from 1999 to early 2019. Mapping is based on the level of publisher accreditation, research topics, theories used, research methods, research units, the total number of years of analysis, sample size, research variables, tax avoidance proxy, and test results. This study uses a qualitative method with a bibliographic approach. The objects used in this study are 105 research articles published by SINTA accredited journals (Indonesia Reputable Journals) as well as Scopus indexed journals. The results show that the majority of publisher accreditation levels are SINTA 2 and SINTA 3, and some have been indexed by Scopus. The most discussed research topics are determinants of tax avoidance. Most research uses agency theory as the theoretical basis and uses quantitative methods. The quantitative studies used manufacturing companies listed on the IDX as the unit of analysis with a scope of three years of analysis and an average sample size of 64 companies. The majority of quantitative studies use tax avoidance as the dependent variable and use four independent variables. The most used independent variables are firm size, institutional ownership, audit committee, leverage, and independent commissioner. The majority of testing results on the effect of firm size on tax avoidance show a positive effect. In contrast, the majority of test results on the effect of the institutional ownership, audit committee, leverage, and independent commissioner show no effect.